REGIONAL IMBALANCES IN DISTRIBUTION OF BULGARIAN HEALTH PROFESSIONALS - Maria Rohova (Peytchinski Publishing, 2017)
Introduction: There are many factors influencing health inequities; health workforce availability and skill mix are among them. Regional distribution of health workers determines access to health services. The aim of this study is to analyse and to assess the distribution of health professionals among the statistical regions and districts in Bulgaria. Methods and materials: The current study uses health professionals to population ratio, Gini index and Lorenz curve to measure and assess the proportionality of health workers distribution. Data are provided from the National Statistical Institute and European Health for All databases. Results and discussion: In Bulgaria, health professionals per population ratio are comparable with the EU average except for the nurses. Beside the shortage of nursing professionals, geographically uneven distribution of health workers is among the main challenges in human resource management.Regional imbalances are significant among the districts in the country. More than half of the physicians are concentrated in 6 districts. The analysis shows an upward trend in imbalances, expressed as absolute or relative differences.The distribution of dentists is much more variant and diverse than this of physicians. The values of Gini index for specialised medical care also reveal considerable imbalances. Conclusions: Differet coefficients have proved the unequal distribution of health workers among the districts.Regional imbalances are not the only reason for health inequities in Bulgaria but they have significant influence in rural and remote areas and in regions with high unemployment, low incomes and ageing population.